Karakteristik Fisik Santan Kelapa dengan Penambahan Emulsifier Biji Ketapang - Yulindha Yulindha; Anang Mohamad Legowo; Nurwantoro Nurwantoro (Universitas Muhammadiyah Semarang, 2021)
The purpose of this research was to determine the influence of the addition of ketapang seed emulsifier on the physical properties of coconut milk. Completely Randomized Design (CDR) with 4 treatments and 5 repetitions were used in this research. The addition of seed ketapang emulsifier with different concentrations of 0%, 0,5%, 1% and 2%. The data emulsion stability test were analyzed using descriptive analysis. The data of adhesiveness, viscosity, whiteness and pH value obtained were further processed by Analysis of Variance to determine the effect of treatment. If there was any significant effect of treatment then it was followed by Duncan’s Multiple Range Test. The result showed that the addition of ketapang seed emulsifier had an influence on emulsion stability as well as an influence (P < 0,05) on the adhesiveness, whiteness and pH value of coconut milk but there was no influence P > 0,05) on the viscocity. Overall, the seed ketapang emulsifier can increase emulsion stability and adhesiveness while the whiteness and pH value of coconut milk decreased. The best treatment based on all parameters was the addition of ketapang seed emulsifier 0,5% concentration.